Repellency, contact toxicity, and anti‐oviposition effects of three ethanol‐extracted plant essential oils on Bemisia tabaci (Hemiptera: Aleyrodidae). Issue 6 (8th November 2022) - Wagan, Tufail Ahmed; Hua, Hongxia; Bozdoğan, Hakan; Khan, Muhammad Musa
Abstract: There are more than 1200 species of whiteflies found across the globe. Due to the high level of resistance of whitefly against synthetic insecticides, alternate pest management measures have their significance. Plant essential oils (EOs) affect insect pests in many ways, such as via stimulatory, deterrent, toxic, and hormonal effects. This study was designed to determine the repellency of EOs, toxicity, and oviposition deterrent activities of Allium ascalonicum, Cinnamomum camphora, and Mentha haplocalyx against adult whiteflies. In repellency determination experiments, a single tomato plant was treated with 10 ml of ethanol‐extracted EO with 1000 ppm concentration. Results showed that C. camphora EO was the most repellent for whitefly compared to M. haplocalyx and A. ascalonicum . The oviposition deterrent experiments revealed that C. camphora has the highest oviposition deterrent effect, followed by M. haplocalyx and A. ascalonicum . A single plant treatment method was used to assess the contact toxicity of three EOs against whitefly after 12, 24, 48, and 72 h of exposure. The results revealed that C. camphora is more toxic to whitefly than M. haplocalyx and A. ascalonicum . After determining the antagonistic effects of these EOs, the oils were analyzed using gas chromatography/mass spectrometry to identify the chemical components. It can be concluded that C. camphora is the most effective oil EO in terms of toxicity, repellence, and oviposition deterrence, followed by M. haplocalyx and A. ascalonicum under greenhouse conditions. Our results introduce some new eco‐friendly plant EOs to control whiteflies.